An approach to synthesise safe systems. (7th September 2006) - Jhumka, Arshad; Freiling, Felix; Fetzer, Christof; Suri, Neeraj
Detectors are system components that identify whether the system is in a particular state. Detectors can be used to ensure arbitrary safety properties for systems, hat is, they can be used to prevent the system from reaching a 'bad' state. Detectors have found application in the area of fault-tolerant systems but can also be used in the area of security. We present here a theory of detectors that identifies the class of perfect detectors and explains their importance for fault-tolerant systems. Based on the theory, we develop an algorithm that automatically transforms a fault-intolerant program into a fault-tolerant program that satisfies its safety property even in the presence of faults. We further show how to use some of the results for adding security properties to a given insecure program. We provide examples to show the applicability of our approach.